Whisker of trouble - Ryan, Sofie, 1958- (Ryan, Sofie, 1958- Second Chance cat mystery., 2016)
"Sarah is turning her keen eye to the estate of collector Edison Hall, hoping for fabulous finds for Second Chance...but when her rescue cat, Elvis, discovers a body in the kitchen, everything goes paws up. The body belongs to an appraiser who had been hired to check out Edison's wine collection. When Edison's sister shows up at Second Chance, she hires Sarah's friends...the kooky and charismatic trio of ladies who call themselves Charlotte's Angels and work out of the shop...to solve the murder, Sarah knows she and Elvis are only going to get deeper into the case. But as it becomes a cat and mouse game of lies, cons, cheats, and family squabbles, can Elvis and Sarah claw their way to the truth before the killer slinks away forever?